The influence of counselling self-efficacy and coping on stress among counselling practicum students - Alosius, Mauren Alma; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohamed, Yusni; Engku Kamarudin, Engku Mardiah (Human Resources Management Academic Research Society (HRMARS), 2023)
Self-efficacy is a critical factor in motivating counselling students to persevere through stressful events during their training period. Studies have also found good coping mechanisms to be vital for individuals to manage their stress. This study analysed the influence of counselling self-efficacy and coping on stress among counselling practicum students in a Malaysian public university. A total of 88 respondents participated in this study. Three instruments were used, namely the Perceived Stress Scale-10, Counselling Activity SelfEfficacy Scale and Brief Resilient Coping Scale, to measure stress, counselling self-efficacy and coping. The descriptive analysis was conducted to identify the mean score and standard deviation of each variable. The independent sample T-test revealed no significant difference between the mean stress scores according to the demographic of the students. Pearson correlation indicated significant relationships between counselling self-efficacy and coping with stress. Significantly, counselling self-efficacy had a major influence on stress, indicating that higher counselling self-efficacy contributes to lower stress among the counselling practicum students. Suggestions were provided to help counselling students tolerate stress by encouraging increased counselling self-efficacy skills and positive coping mechanisms.